Kalevala, kansanrunous ja kirjakieli - Punttila, Matti; Issakainen, Touko (Virittäjä, 2003)
The Kalevala, folk poetry and written Finnish (englanti) 2/2003 (107) The Kalevala, folk poetry and written Finnish The article examines the influence of the Kalevala, especially its first edition (the Old Kalevala), on the formation of written Finnish, looking at phonology, morphology, word formation and, above all, lexical development. The most important research material used is the corpus of nineteenth century texts available through the Research Institute for the Languages of Finland. The phonological and morphological influences of the Kalevala on written Finnish have neither been very great nor lasting. Nevertheless, developments such as the consolidation of the ts consonant combination, the use of the -tta and -tt forms for the abessive case, and, perhaps to an extent too, the spread of certain prolative forms, can all be attributed in part to the Kalevala. The biggest influence of the Kalevala, however, has been on the lexical development of written Finnish. The writers estimate that the Dictionary of Modern Finnish (1951-1961) contains 184 words whose first literary appearance was in the Old Kalevala, and a further 197 words that were used not only in the Old Kalevala but also before that, in folk poetry collections or other early nineteenth century literature (but not in material dating from the period of Swedish rule, i.e. prior to 1809). These include surprisingly common words, such as ers a certain, one, kuten as, such as, jrjest to organise, arrange and joten [and] so, thus. Of approximately 380 neologisms in the Kalevala, 212 (or almost 56 per cent) got as far as the Basic Dictionary of Finnish (1990-1994), which is considerably more concise than the Dictionary of Modern Finnish. The importance of the Kalevala for word formation can be seen in, for instance, the spread of various bahuvrihi compounds (e.g. kyrmyniska: bulge + neck a person with a bulging neck; tuliter: fire + blade brand-new, tuppisuu: case/cover + mouth a taciturn person/tongue-tied). Many types of derivative have become familiar to Finns specifically through the Kalevala and other folk poetry collections. Especially common examples from the Kalevala include the diminutive suffixes -inen, -nen, -ut/-yt, other nominal suffixes such as -in, -kko/-kk, -elma/-elm, -nta/-nt, the moderating adjectival suffixes -hka/-hk and -hko/-hk, and the equative suffix -uinen/-yinen. The most important of the verbal suffixes in the Old Kalevala are the frequentative -ele and the momentaneous -ahta/-ht and -ise. Matti Punttila, Touko Issakainen Kielenainekset -AhtA- (kieli: suomi, sivulla: 242) -AhtA- (kieli: suomi, sivulla: 243) -eA (kieli: suomi, sivulla: 240) -ele- (kieli: suomi, sivulla: 240) -ele- (kieli: suomi, sivulla: 241) -ele- (kieli: suomi, sivulla: 243-) -elmA- (kieli: suomi, sivulla: 240) -elmA- (